Low earth orbit design for remote sensing applications - Okasha, Mohamed Elsayed Aly Abd Elaziz; Kamalaldin, Karim (2013)
This paper investigates the orbit design procedures of a remote sensing satellite mission. The mission objective is to gather images over an area of interest for a variety of applications such as land monitoring, digital mapping, minerals exploration, and deforestation. The design procedures are mainly driven by the payload performance, the satellite life time and the coverage requirements. For numerical analysis, the payload is considered to be a pushbroom imagining system that produces high resolution with 2.5 m and 5 m ground sample distance in one panchromatic and four multi-spectral bands respectively and it is assumed to image the Earth surface in latitude range from 22 to 32 N. Matlab and STK software are employed to define the initial orbit design that can meet the mission requirements.